The Management of IAIN Ponorogo-Assisted Madrasas: Religious, Populist, Center of Excellence, Diversity - Mukhibat Mukhibat; Muhammad Fahim Tharaba; Munair Yusaf Abdalhafiz Salah (Cendekia: Kependidikan dan Kemasyarakatan, 2020)
The current various madrasa innovations remain various problems, namely being at a crossroads between maintaining the original character and modernization. MAPK faces problems with formal legal aspects, MA Skills and Models have funding problems, and Madrasa Diniyah is experiencing problems in certificate recognition. Qualitative research on the vision of madrasa development is very important so that the various models of madrasacontinue to develop according to their historical character and vision. Madrasamust be built based on Islamic values, the essential character of the history of Islamic education, and the formulation of future challenges. Islamic and populist characters in madrasas are identities that must color the curriculum. Madrasas are obliged to carry out the basic vision and mission of pesantren, namely tafaqquh fi al-din by 1) increasing community participation in empowering accountable, quality-oriented management, which will encourage madrasato be the centerof excellence. 2) increasing participation so that madrasas remain the core of a learning society, capable, functional, integrated.Berbagai inovasi madrasah yang ada sekarang ini,ternyata masih menyisakan berbagai persoalan, yakni berada dalam persimpangan jalan antara mempertahankan karakter asli dan melakukan modernisasi. MAPK mengadapi problem aspek legal formal, MA Keterampilan dan Model mengalami problem pendanaan, dan Madrasah Diniyah mengalami problem pengakuan ijazah. Penelitian kualitatif tentang visi pengembangan madrasah menjadi sangat penting dilakukan agar berbagai model madrasah tersebut tetap berkembang sesuai karakter dan visi historisnya. Madrasah harus dibangun berdasarkan nilai-nilai Islam, karakter esensial dari sejarah pendidikan Islam, dan rumusan tantangan masa depan. Karakter Islami dan populis pada madrasah merupakan identitas yang harus mewarnai kurikulumnya. Madrasah berkewajiban mengemban visi misi asasi pesantren, yaitu tafaqquh fi al-din dengan melakukan 1) peningkatan partisipasi masyarakat dalam pemberdayaan manajemen yang accountable, quality oriented, yang akan mendorong madrasah menjadi centers of excellence. 2) peningkatan partisipasi agar madrasah tetap menjadi core dari learning society, capable, fungsional, integrated.